Operasi Pasar Murah PT. Pos Indonesia: Upaya Meningkatkan Kesejahteraan Masyarakat di Bulan Ramadhan - Dedek Jihan Nasution; Fajar Utama Ritonga (CV Edujavare Publishing, 2025)
This research examines the implementation of the subsidized market operation program conducted by PT. Pos Indonesia (Persero) in Medan during Ramadan 2025. This program represents a strategic effort to address price fluctuations and ensure the availability of essential goods at affordable prices for the community, especially approaching the holy month of Ramadan and Eid al-Fitr. Using a qualitative approach through observation, in-depth interviews, and documentation studies, this research analyzes the implementation mechanisms, cross-sectoral coordination, and the socio-economic impact of the program on community welfare. The findings indicate that the subsidized market operation has successfully increased community purchasing power, stabilized food prices in the market, and strengthened community social cohesion. The application of the Community Organization Community Development (COCD) intervention method through student volunteer involvement has enhanced the social empowerment dimension of this program. Nevertheless, several challenges were identified in its implementation, such as stock limitations, long queues, and limited coverage. This research recommends expanding program coverage, diversifying commodities, integrating digital services, and developing partnerships with local Small and Medium Enterprises (SMEs) to improve program effectiveness within the welfare state framework as a manifestation of state-owned enterprise social responsibility.